2017
DOI: 10.1200/jco.2017.35.15_suppl.e20087
|View full text |Cite
|
Sign up to set email alerts
|

Priming PD-L1 expression by chemotherapeutic agents in non-small cell lung cancers.

Abstract: e20087 Background: Immunotherapy targeting PD-1/PD-L1 axis has yielded fruitful results in non-small cell lung cancers (NSCLCs). Evidences showed that treatment responses are likely correlated with tumor PD-L1 expression levels, which is especially true in the first line setting. Results from Keynote-021 suggested that pembrolizumab plus platinum-pemetrexed doublet came out with better overall response rate and progression free survival as compared to chemotherapy alone even in the PD-L1 low-expression group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In particular, it has recently been shown that PD‐L1 significantly increased on residual disease after NACT compared with baseline in a large retrospective cohort of patients with TN early BC . The induction of PD‐L1 expression by chemotherapy is consistent with observations in other cancer types and with the notion that chemotherapy is able to induce an adaptive immune response through various mechanisms, including immunogenic cell death and the activation of the damage response c‐GAS/STING . Indeed, it has been shown that CT may boost the immunogenicity of the tumor by increasing tumor immune infiltrate from baseline to post‐NACT samples, with a high rate of conversion from low‐TIL to high‐TILs tumor .…”
Section: Methodssupporting
confidence: 71%
“…In particular, it has recently been shown that PD‐L1 significantly increased on residual disease after NACT compared with baseline in a large retrospective cohort of patients with TN early BC . The induction of PD‐L1 expression by chemotherapy is consistent with observations in other cancer types and with the notion that chemotherapy is able to induce an adaptive immune response through various mechanisms, including immunogenic cell death and the activation of the damage response c‐GAS/STING . Indeed, it has been shown that CT may boost the immunogenicity of the tumor by increasing tumor immune infiltrate from baseline to post‐NACT samples, with a high rate of conversion from low‐TIL to high‐TILs tumor .…”
Section: Methodssupporting
confidence: 71%
“…Previous reports showed that prior chemotherapy enhanced the therapeutic outcome of immunotherapy (18)(19)(20)(21)(22), which also reversed chemoresistance after prolonged chemotherapy (20,23). Although some chemotherapeutic drugs have modest activity when used as single treatments, their combination with immunotherapy may result in enhanced anticancer effects and can be used to promote an immunogenic tumor phenotype (24)(25)(26). In addition, engineered delivery vehicles and scaffolds are increasingly considered as promising tools for transporting immunotherapeutics (27)(28)(29)(30)(31)(32)(33), with decreased systemic toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…However, those blockade therapy still suffer from low immune response rate because of low neoantigen burden and tumor immunogenicity . Based on this problem, previous researches showed that chemotherapy could strengthen the effects of immunotherapy, which in reverse reduced chemoresistanse after long‐term chemotherapy . Although chemotherapy has modest effects when served as single treatments, their synergy with immunotherapy may provide enhanced antitumor effects because of immunogenic cell death (ICD) induced by chemotherapy …”
Section: Introductionmentioning
confidence: 99%